Directions in Software Development and Maintenance - Biggerstaff, Ted J. (Institute of Electrical and Electronics Engineers, Inc., 1993)
Development environments are entering a period of dramatic change. A major component of this change is a reorientation toward domain driven development environments including an integration of domain oriented support tools. This reorientation will bring about a decline in the role of conventional programming languages and at the same time, force an evolution toward more abstract programming representations – more abstract in the sense that most of the implementation details (as we know them today) will be abstracted away. Thus, development is moving farther away from conventional software engineering models and closer to the problem.